PROBLEM TERMINOLOGI MODERAT DAN PURITAN DALAM PEMIKIRAN KHALED ABOU EL-FADL - Muhammad Nur (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2013)
The war of ideas which happen today is more than just the battle of arguments, concepts, or ideas. Moreover, the terminology of a word is also be a battle of the idea. The war of terminology raised new terminologies derived from Western worldview, which is not in accordance with Islam. In the end, Western terminology related to Islam raised a lot of debate and discourse among scholars. As we know, the West has its own valuesand worldviews on life, which certainly have an impact on ideas, and ideologies. Surprisingly, lot of Muslim scholars used the western terminology in some of their ideas. One of them is Khaled Abou el-Fadl. In this article, the author tries to study the moderate and the puritan terminology created by Khaled Abou el-Fadl. He was a contemporaryIslamic thinker from Kuwait. With both of the terms (moderate and puritan), he has dichotomized Muslims into two distinct groups. This paper will try to describe the problem of moderate and puritanical in Khaled Abou El Fadl’s thinking and its implication to the Islamic Ummah.